Detection of Capsular Antigen Production in Unencapsulated Strains of Staphylococcus aureus - Yoshida, Kosaku (1974)
Of 91 compact-type strains of Staphylococcus aureus in regular serum soft agar (SSA), 82 converted diffuse-type growth in serum soft agar (pH adjusted to 6.0). With the addition of four different rabbit anticapsular sera (anti-type A, B, C, and D sera) in low pH (6.0) SSA, 21 strains of S. aureus showed compact-type colonial morphologies. Eleven, one, and one strains of S. aureus reacted singly with rabbit anticapsular sera types A, B, and C, respectively, and no strain reacted with rabbit anticapsular type D. Eight of the e strains reacted with both rabbit anticapsular sera types A and B. When the ability to absorb the converting activities of the antisera (changes of colonial morphologies of anticapsular sera in SSA) was quantitatively tested, 7- to 27-fold of these organisms were capable of absorbing the activities compared with the Smith diffuse organisms. These results suggest that even unencapsulated S. aureus strains are capable of producing capsular substance, although the capability is quantitatively different from strain to strain.